2023
DOI: 10.1186/s12933-022-01730-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in selenium deficiency is associated with metabolic syndrome and prevalence of heart disease

Abstract: Background Serum selenium levels have been associated with the incidence of heart failure (HF) and signs of the metabolic syndrome. In addition, notable differences have been reported between males and females in food intake and micronutrient metabolism, possibly explaining different health outcomes. Objective Our objective was to elucidate sex-specific, cross-sectional phenotypic differences in the association of serum selenium concentrations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…We observed that low blood selenium levels were associated with heart failure, which is consistent with the results of the BIOSTAT-CHF cohort study [38] and Yang L et al [39]. A meta-analysis showed the standard mean deviation (SMD) of selenium levels in heart failure patients were significantly lower than the healthy control group (SMD=-0.98, 95% CI: -1.34, -0.62) [39].…”
Section: Discussionsupporting
confidence: 89%
“…We observed that low blood selenium levels were associated with heart failure, which is consistent with the results of the BIOSTAT-CHF cohort study [38] and Yang L et al [39]. A meta-analysis showed the standard mean deviation (SMD) of selenium levels in heart failure patients were significantly lower than the healthy control group (SMD=-0.98, 95% CI: -1.34, -0.62) [39].…”
Section: Discussionsupporting
confidence: 89%
“…The database for Se and hypertension is less well investigated, particularly with regard to serum SELENOP, as most studies investigated total Se only [ 21 , [43] , [44] , [45] , [46] ]. Nawrot et al demonstrated a higher risk of high blood pressure with low blood Se levels, which was specific to men [ 43 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research has demonstrated that Se status was associated with obesity, a chronic disease linked to inflammation, where either neutral or beneficial effects were observed with supplementation [ 11 , 28 , 29 ]. Interestingly, the available data indicate that sexual dimorphism plays a role in determining disease outcome; here lower Se status was linked to a higher BMI and increased risk of diabetes and reported incidences of myocardial infarction in females, yet the opposite was determined in males [ 30 ]. Conversely, contemporary research found that Se supplementation did not modulate oxidative damage and cellular proliferation within breast tissues in patients with an increased risk of breast cancer [ 31 ].…”
Section: Introduction Of Seleniummentioning
confidence: 99%